Introduction - Zúquete, J.; Marchi, R. (Global identitarianism, 2023)
The rise of Identitarianism is inseparable from Europe’s demographic winter – the dramatic drop in the birth rate and the aging of the European native population – which in tandem with the phenomena of mass immigration into Europe and the growth of foreign-born populations and cultural and religious diversity serve as the setting in which groups of Identitarians see themselves not simply in a run-of-the mill political battle but in a transcendental civilizational struggle in which the literal survival of European cultures and peoples is at stake. Identitarians believe that they are engaged in a cultural combat that is laying the groundwork for such restoration and regeneration. Global Identitarianism offers the first global overview of the Identitarian movement that first began spreading within Europe in the earliest years of 21st century with the self-declared aim of protecting the ethnic and cultural identity of Europe from the onslaught of globalism and mass immigration.